2017
DOI: 10.1007/s11262-017-1528-x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of the spike gene of the porcine epidemic diarrhea virus in Mexico, 2013–2016

Abstract: In Mexico, the first outbreaks suggestive of the circulation of the porcine epidemic diarrhea virus (PEDV) were identified at the beginning of July 2013. To identify the molecular characteristics of the PEDV Spike (S) gene in Mexico, 116 samples of the intestine and diarrhea of piglets with clinical signs of porcine epidemic diarrhea (PED) were obtained. Samples were collected from 14 farms located in six states of Mexico (Jalisco, Puebla, Sonora, Veracruz, Guanajuato, and Michoacán) from 2013 to 2016. To iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 37 publications
0
27
0
3
Order By: Relevance
“…The PEDv S gene was amplified by endpoint RT‐PCR, yielding 28 positive samples (52.83%) from 10 of the 17 states sampled. This study reports the presence of the PEDv S gene in the states of Hidalgo, Oaxaca and San Luis Potosí for the first time (Lara‐Romero et al, ; OIE, ). The coronavirus S protein is a type I membrane glycoprotein that interacts with cell receptors during virus entry (Weiss & Leibowitz, ).…”
Section: Resultsmentioning
confidence: 84%
See 3 more Smart Citations
“…The PEDv S gene was amplified by endpoint RT‐PCR, yielding 28 positive samples (52.83%) from 10 of the 17 states sampled. This study reports the presence of the PEDv S gene in the states of Hidalgo, Oaxaca and San Luis Potosí for the first time (Lara‐Romero et al, ; OIE, ). The coronavirus S protein is a type I membrane glycoprotein that interacts with cell receptors during virus entry (Weiss & Leibowitz, ).…”
Section: Resultsmentioning
confidence: 84%
“…Various genotypes of the S protein gene have been described based on their genetic traits and the period when the strains emerged: GIa (classical), GIb (emergent, Indel‐S), GIIa (emergent, non‐Indel‐S from the Americas) and GIIb (emergent, non‐Indel‐S from Asia) (Jarvis et al, ; Lee, ). Previous studies in Mexico have identified circulating strains with a GII genotype (from the Americas) as well as strains with a GI genotype (Indel‐S) (Lara‐Romero et al, ). The 20 strains isolated in this study (Table ) are in the GIIa genotype branch and were identified as emerging, non‐Indel‐S variants (Figure ); the strains PEDv/MEX/JAL/LI‐DMZC11/2015 and PEDv/MEX/MICH/LI‐DMZC19/2015 are located in a cluster related to emerging strains from Asia, and all other strains are in clusters along with strains from the Americas (Jarvis et al, ; Lee, ), indicating that a wide range of strains are circulating in Mexico.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…PEDV variants emerged in the United States starting in May 2013 and then spread rapidly throughout the nation. Many American, Asian and European countries, including Canada, Mexico, Colombia, Japan, South Korea, the Philippines, Thailand, Germany, the Netherlands and Switzerland have also reported outbreaks of PED [6,[8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%